Michael Cimino's Heaven's gate - Cimino, Michael 1939-2016; Carelli, Joann; Mansfield, David 1956-; Kristofferson, Kris 1936-2024; Walken, Christopher 1943-; Hurt, John 1894-1966; Waterston, Sam 1940- (Twentieth Century Fox Home Entertainment, 2012)
A Harvard graduate, turned federal Marshal in Wyoming, learns of a government sanctioned plot by cattle barons to kill the area's European settlers for their land. The resulting battle is based on the Johnson County War of 1892
DVD, NTSC, region 1 ; widescreen (2.40:1) presentation ; Dolby digital 5.1 surround. - Originally produced as a motion picture in 1980. - Special features: Disc 1: Cimino and Carelli [2012 audio conversation]. Disc 2: Interviews: Kris Kristofferson, David Mansfield, Michael Stevenson; Restoration demonstration; Teaser; TV spot
Orig.: USA, 1980
Music by David Mansfield ; art director, Tambi Larsen ; editor, Tom Rolf [and others] ; director of photography, Vilmos Zsigmond
Disc one : Director's cut of Part 1; illustrated audio interview with director and producer -- Disc two : Director's cut of Part 2; interviews of actor, assistant director, performer and soundtrack arranger; restoratin demonstration; teaser and TV spot
Keywords: Geschichte 1800-1900; Cattle stealing / Wyoming / Drama; Immigrants / Wyoming / Drama; Johnson County War, 1892 / Drama; Ranchers / Wyoming / Drama; Einwanderer; Geschichte; Wyoming / History / 19th century / Drama; Film